Role of probiotics in prevention of necrotizing enterocolitis in preterm neonates - S, Chandrashekar G; Shettigar, Sanchita; Varghese, Tharun C (Indian Journal of Child Health, 2018)
Background: Necrotizing enterocolitis (NEC) is one of the common emergencies in preterm neonates which are associated with high morbidity and mortality despite recent advances in neonatal care. Probiotics may be one of the most effective therapies for the prevention of NEC. Objective: The objective of this study is to evaluate the role of probiotics in reducing the incidence of NEC in preterm newborns. Methods: This was a prospective randomized control study conducted at tertiary care teaching hospital. A total of 140 preterm newborns of gestation ?34 weeks of age were enroled in the final analysis. The recruited newborns were randomized into intervention group and control group by simple random sampling method. The intervention group was fed probiotics mixed with expressed breast milk, and the control group was fed with milk alone. Result: The incidence of NEC in probiotics group was significantly lower than in the control group (2.86% vs. 11.43%), (p=0.04). Although there were no significant differences in the initial presentation of NEC between the two groups, those in the study group who developed NEC had less severe disease, based on Bell’s staging criteria. There was no significant difference in terms of age in diagnosis of NEC and in age at which birth weight is gained between the two groups. However, there was a statistically significant difference in duration of hospital stay (15.62±2.84 vs. 23.54±3.43 days; p